The association of personality dimensions, perceived stress and emotion regulation to driving anger among taxi drivers in Iran - Barahmand, Usha; Nabidoost, Alireza; Daryadel, Seyed Javad (Penerbit Universiti Kebangsaan Malaysia, 2016)
The purpose of the present study was to determine the associations of personality dimensions, perceived stress and emotion regulation to driving anger among taxi drivers in Iran. Using a convenience sampling procedure, a number of 120 taxi drivers were recruited for the study. Data were collected using a sociodemographic data sheet, the HEXACO personality inventory, the perceived stress scale, the cognitive emotion regulation questionnaire and the driving anger scale. The data were analyzed using Pearson’s correlation coefficients and multiple regression analysis. Findings revealed that 5% to 20% of taxi drivers experience high levels of anger while driving. Most taxi drivers agree that slow driving and traffic obstructions as frustrating and anger-provoking. The drivers reported experiencing stress frequently. The personality dimensions of extroversion, agreeableness and honesty/humility were found to be associated with anger specifically related to the presence of police. Among the cognitive emotion regulation strategies, only catastrophizing and positive refocusing were found to be associated with driving anger from the involvement of police. Perception of stress, extroversion and conscientiousness and positive refocusing together explained 19.1% of the variance associated with anger elicited by driving situations, with the personality traits making the largest contribution.